Sonic boom. Go team Sonic! [videorecording (DVD)] (Sonic boom (Television program), 2019)
It's a Sonic never seen before, an ensemble comedy that pokes fun at action-adventure storytelling. Wherever he goes and whatever he's up against, Sonic the Hedgehog is aided by his sidekick, Tails, and his friends Knuckles, Amy, and Sticks, and attacked by his arch-nemesis, Dr. Eggman. Join Sonic and the gang as they accept a dare from Dr. Eggman. Tag along with Sonic and Knuckles as they enter a game show. Find out what happens when Sonic's status as the town's biggest hero is threatened.